Navigating educational mistakes in learning: Cultural perspectives of Emirati students and expatriate instructors in higher education - Williams, Cara D; Hojeij, Zeina; Johnson, Jason; Eppard, Jenny; McKeown, Kara (Journal of International Students, 2025)
This study examined the cultural perceptions of mistakes in learning within higher education classrooms in the United Arab Emirates (UAE) among Emirati students and expatriate instructors. This study revealed an interplay of cultural norms, teaching practices, and mistaken culture in learning. While instructors emphasized the importance of embracing mistakes as tools for reflection and growth, many students associated mistakes with embarrassment and fear of judgment, reflecting broader cultural attitudes. Contrasting views on the roles and relationships between students and instructors were highlighted, with expatriate educators adopting facilitative teaching approaches and students often perceiving instructors as authoritative figures. The findings underscore the need for culturally responsive teaching strategies to foster a positive mistake culture and bridge the gap between pedagogical practices and student expectations. The implications provide valuable insights for international educators and policymakers striving to create inclusive and effective learning environments in culturally diverse contexts.